2015
DOI: 10.1167/15.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Mixed emotions: Sensitivity to facial variance in a crowd of faces

Abstract: The visual system automatically represents summary information from crowds of faces, such as the average expression. This is a useful heuristic insofar as it provides critical information about the state of the world, not simply information about the state of one individual. However, the average alone is not sufficient for making decisions about how to respond to a crowd. The variance or heterogeneity of the crowd--the mixture of emotions--conveys information about the reliability of the average, essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 52 publications
0
67
2
Order By: Relevance
“…The results of all four groups are similar, with only minor differences in speed or accuracy, but all showing the same essential effects described in the preceding paragraph. Our results should be considered in light of contrasting findings suggesting that set mean perception and outlier ''pop-out'' accuracy decrease with set variance (e.g., see Dakin 2001;Rosenholtz, 2001;Haberman et al, 2015). For set mean, the type of elements being averaged may be important; line, circle, or face elements may be different than Gabor patterns, which lack clear borders and may cluster when crowded so that stimulus noise becomes critical.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results of all four groups are similar, with only minor differences in speed or accuracy, but all showing the same essential effects described in the preceding paragraph. Our results should be considered in light of contrasting findings suggesting that set mean perception and outlier ''pop-out'' accuracy decrease with set variance (e.g., see Dakin 2001;Rosenholtz, 2001;Haberman et al, 2015). For set mean, the type of elements being averaged may be important; line, circle, or face elements may be different than Gabor patterns, which lack clear borders and may cluster when crowded so that stimulus noise becomes critical.…”
Section: Discussionmentioning
confidence: 74%
“…Observer reports of set statistics include set feature variance or range, as shown directly (Morgan, Chubb, & Solomon, 2008;Solomon, 2010;Haberman, Lee & Whitney, 2015) and as evidenced by their reporting presence or absence of items depending on their being within or outside the range, respectively (Pollard, 1984;Dakin & Watt 1997). Recently, Khayat and Hochstein (2018) reported that observers perceive not only set mean but also set range, implicitly, automatically, and on-the-fly, on a trial-by-trial basis.…”
Section: Introductionmentioning
confidence: 99%
“…For facial features, Haberman, Lee, and Whitney (2015) found observers able to accurately estimate the variance in facial expressions of a group, establishing the visual system's sensitivity to variance in high-level domains. We thus asked whether computation of mean facial attractiveness would be affected by set variance.…”
Section: Set Variance and Ensemble Perceptionmentioning
confidence: 80%
“…It has been previously demonstrated that people can efficiently extract various statistical information form briefly presented multiple items. Summary statistics such as mean and variance can be extracted about various features of individual items from basic sensory dimensions, like orientation (Alvarez & Oliva, 2009;Dakin & Watt, 1997;Morgan, Chubb, & Solomon, 2008;Parkes, Lund, Angelucci, Solomon, & Morgan, 2001;Suárez-Pinilla, Seth, & Roseboom, 2018), size (Ariely, 2001;Chong & Treisman, 2003;Khvostov & Utochkin, 2019;Tokita, Ueda, & Ishiguchi, 2016), color (Bronfman, Brezis, Jacobson, & Usher, 2014;Gardelle & Summerfield, 2011;Maule & Franklin, 2015), to quite complex and high-level dimensions, like facial expression (Haberman, Lee, & Whitney, 2015;Haberman & Whitney, 2007) or animacy (Leib, Kosovicheva, & Whitney, 2016). Interestingly, the efficiency and accuracy of such ensemble representation does not suffer (Ariely, 2001;Chong & Treisman, 2005;Fouriezos, Rubenfeld, & Capstick, 2008;Haberman, Harp, & Whitney, 2009; or even benefits (Chong, Joo, Emmmanouil, & Treisman, 2008;Robitaille & Harris, 2011) from increasing set size, whereas our ability to report individual items quickly degrades with set size (Ariely, 2001;Haberman & Whitney, 2007).…”
Section: Introductionmentioning
confidence: 99%